Strategies for the prevention and mitigation of the desertification process. Study in the middle basin of the Chicamocha river, Colombia (2021)
The insufficiency of instruments oriented to the prevention and mitigation of the desertification process is one of the factors that affect the exacerbation of this environmental problem present in the northeast of Boyacá Department, in the middle basin of Chicamocha River. Based on the above, some strategies that contribute to the management of this process are proposed, considering biophysical, socioeconomic and political-institutional elements of the basin that aim at the consolidation of a tool for the decision making in this regard. The development of the study is synthesized in three stages: 1) identification of the possible strategies to prevent and mitigate desertification, 2) representation and spatial distribution of the potential strategies against the basin deterioration and 3) theoretical-practical evaluation of the strategies. As a result, four strategies were defined, covering sustainable production systems and practices, payment for environmental services schemes, monitoring and early warning systems, and regulatory figures focused on the declaration of protected areas. The biophysical conditions of the basin provide several alternatives for the location of the strategies, in which the use and type of soil coverage and the respective national frameworks are decisive; however, socioeconomic conditions became a possible limitation for its implementation. Finally, most of the strategies are included in the regional planning instruments, which represents a starting point for their eventual execution.